What Can Screen Capture Reveal About Students’ Use of Software Tools When Undertaking a Paraphrasing Task? - Bailey, Carol; Withers, Jodi (Journal of Academic Writing, 2018)
Previous classroom observations, and examination of students’ written drafts, had suggested that when summarising or paraphrasing source texts, some of our students were using software tools (for example the copy-paste function and synonym lookup) in possibly unhelpful ways. To test these impressions we used screen capture software to record 20 university students paraphrasing a short text using the word-processing package on a networked PC, and analysed how they utilised software to fulfil the task. Participants displayed variable proficiency in using word-processing tools, and very few accessed external sites. The most frequently enlisted tool was the synonym finder. Some of the better writers (assessed in terms of their paraphrase quality) availed themselves little of software aids. We discuss how teachers of academic writing could help students make more efficient and judicious use of commonly available tools, and suggest further uses of screen capture in teaching and researching academic writing.